Drgania Wymuszone Parametrycznie w Układzie z Nieliniowa Bezwładnością - Gryboś, R. (Engineering Transactions, 1966)
The conditions of main subharmonic resonance excited parametrically by a harmonic force are studied for a system with nonlinear inertion. First is solved the case when the excitation frequency is twice as great as the natural frequency of the linear system (i.e. without the concentrated mass at the end of the bar). The stability of the solution is investigated. The next case under consideration is that of any excitation frequency. This problem is solved, by means of the perturbation method combined with the method of variation of constants, Solution is found in the first approximation. The stability of the solution is investigated.The case of nonlinear elasticity is also considered.